Farmer Exchange Rate , Government Expenditure On Education And Government Expenditure On Health Of The Human Development Index In North Sumatera Province - Zulkarnain Nasution; Khairul Rizal; Junita Lubis (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2021)
Human development is one of the factors in increasing the implementation of national development. Human development that is carried out can be calculated with the level of human health and standard of living. Then the level of the human development index can also affect the value of increasing per capita income and economic growth. The use of the model in this article was processed with the multiple linear regression program and classical assumptions test data using SPSS 22.The results of the analysis produce farmer value added (X1) which can significantly affect the human development index (Y) in North Sumatra Province, government spending in the education sector (X2) can significantly affect the Human Development Index (Y) in North Sumatra Province and government spending on health sector expenditures (X3) has no significant effect on the Human Development Index (Y) in North Sumatra Province. It shows that government spending in the health sector (X3) has not been properly realized so that it is not strong enough to increase the Human Development index in North Sumatra Province. The results of the research on government spending in the education sector (X1) have a dominant effect in increasing the human development index in the province of North Sumatera.